#### Answer

$(2x-3)(5x-4)$

#### Work Step by Step

$10x^{2}−23x+12$
First, identify two numbers that multiply with each other to become 120, the product of the constant and coefficient of x2 (10 × 12) and add together to become -23, the coefficient of x.
From inspection, we identify these numbers as -15 and -8.
Secondly split the coefficient of x into the sum of the two above numbers.
$10x^{2}−23x+12$
$=10x^{2}+(-15-8)x+12$
$=10x^{2}−15x-8x+12$
Factorize by grouping to find the answer.
$10x^{2}−15x-8x+12$
$=5x(2x-3)-4(2x-3)$
$=(2x-3)(5x-4)$